Prevalence and risk factors of binge eating disorder among medical students: evidence from a cross-sectional study in Vietnam: 10.55131/jphd/2024/220312 - Van, Chuc Dang; Duy Tran Duc; Huong Nguyen Thi; Huong Nguyen Thi Thu; Huong Hoang Thi; Linh Truong Dieu; Trinh Dang Tuan; Anh Doan Bao; Trang Le Ngoc; Tan Chu Khac; Cap Minh, Duc (Journal of Public Health and Development, 2024)
Binge eating disorder (BED) is a significant public health problem worldwide. This cross-sectional study aimed to determine the prevalence of BED and its association among 411 medical students at a medical university in northern Vietnam. Data were collected through face-to-face interviews using structured paper-based questionnaires in a classroom setting. The prevalence of BED symptoms among medical students was 9.5%. Among those with BED symptoms, 7.3% had moderate symptoms, and 2.2% had severe symptoms of BED. Multivariable logistic regression analysis showed that being female (AOR = 3.71; 95%CI: 1.48–9.34), being overweight/obese (AOR = 4.14; 95%CI: 1.39–12.32), and being depressed (AOR = 4.05; 95%CI: 1.97–8.33) were associated with an increased risk of BED. This is the first study to provide new insights into the prevalence of BED symptoms and contributing factors among Vietnamese medical students. The findings from this study may assist public health professionals in developing strategies to reduce the risks associated with BED.